PENGELOLAAN DANA DESA DI MASA PANDEMI COVID-19 DESA TIRTOSARI KECAMATAN KRETEK KABUPATEN BANTUL - Lilik Ambarwati; Lukia Zuraida (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
The purpose of this research is to know the village fund management during the Covid-19 pandemic in Tirtosari village Kretek district Bantul aims to evaluate the management of Dana Desa during the Covid-19 pandemic. This research is a qualitative descriptive study. The data collected is in the form of Dana Desa management data in Tirtosari village. Data collection methods used are interview, documentation, and observation. Documents in the form of APBDes and APBDes Realization report for 2020. As subjects and informants were the Tirtosari village apparatus starting from the Village Head, Viilage secretary, head of government, community leaders, religious leaders involved in managing Tirtosari village funds, as well as staff from th Bantul Regency village administration. Based on the result of research and data analysis, it is concluded that the management of Dana Desa includes three stages. (1) The planning process has gone through village deliberations, and has seen conditions in the field and in in accordance with existing regulations. (2) the implementation process is carried out based on applicable regulations, assisted by village assistants who direct and the role of the sub-district which assists the village government in formulating policies and changes in accordance with applicable regulations, and (3) the supervision/accountability process runs in accordance with statutory procedures, the community is also involved in supervising the management of Dana Desa, assisted by the preparation of accountability report using the sistem keuangan desa (Siskeudes).